FUNCTIONAL ACTIVITY OF THE PHAGOCYTEC SELLS AT PATIENTS WITH MAXILLARY SINUSITIS SUFFERING FROM DIABETES - Ognivenko, E.V.; Popov, N.N.; Romanova, E.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Рhagocytec activity of the neutrophilic granulocytes at patients with maxillary sinusitis suffering from diabetes have been investigated. The following phenomena are observed at patients with chronic purulent maxillary sinusitis suffering from insular diabetes: depression of phagocytec of neutrophilic granulocytes and monocytes; distirbance of the process of bacteria capture and killing; depression of oxidase microbicidal system and activity of the receptor system.